2005
DOI: 10.2223/jped.1406
|View full text |Cite
|
Sign up to set email alerts
|

The pediatrician and traffic safety

Abstract: Traffic-related mortality rates are still very high and show the necessity to intensify educational campaigns for community awareness, in addition to encouraging investments in effective pedestrian safety. The pediatrician s role is to decrease the number of children and adolescents who get involved in traffic accidents by providing them with traffic guidance and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies about it in the Brazilian literature are scarce considering the relevance of this topic (14) . Several studies that included vehicles involved in crashes found that the correct use of restraints, as well as the transportation of children in the rear seat, significantly reduces the risk of death and injuries due to accidents (5,15,25) . As a result of inadequate transportation, children may have major trauma in crashes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies about it in the Brazilian literature are scarce considering the relevance of this topic (14) . Several studies that included vehicles involved in crashes found that the correct use of restraints, as well as the transportation of children in the rear seat, significantly reduces the risk of death and injuries due to accidents (5,15,25) . As a result of inadequate transportation, children may have major trauma in crashes.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, studies confirmed the importance of educational strategies to minimize risks (6,8,11,27) . Therefore, traffic education should begin in infancy, in the family, so that, based on the example of people with whom the child lives, the percentage of individuals that transport children in vehicles adequately increases (5,11) . Despite these conclusions, our findings are not easily generalized because our study did not calculate sample size, the sample of motorcyclists was small, and there are few Brazilian studies about the same topic for comparison of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation